Reception of Vilyuy Expedition in Fixation of Folklore of Peoples of Yakutia (1930ies-1970ies) - O. I. Charina; A. S. Larionova; V. A. Petrova (Научный диалог)
The issue of reception of field research of Savvin - Bolo Vilyuy expedition (1938) with subsequent fixation of Russian and Even folklore as well as Yakut folk songs is covered. Internal connections between Vilyuy and the subsequent folklore expeditions organized in 1930-1970 by S. I. Bolo, T. A. Shub, V. D. Lebedev and M. N. Zhirkov are defined. It is shown that within the framework of the Vilyuy expedition of 1938, approaches and principles of fixation of samples of oral folklore were developed, and then these developments were used when collecting text and musical folklore by participants of subsequent expeditions, the principles and approaches being improved. The novelty of the study is due to the fact that the value of the results of the Vilyuy expedition of 1938 to the present time has not yet been considered in science in the stated perspective of continuity. The authors dwell on the issues of formation of the expedition participants as scientists, on the peculiarities of expeditions organization, the tasks set in the framework of expeditions, on the content and composition of the material recorded in the field. The estimation of the achievements of expeditions organized by T. A. Shub, V. D. Lebedev, M. N. Zhirkov is given.